Study of phase formation and atomic transport in ion implanted and irradiated alloys - Jagielski, Jacek (Kovine zlitine tehnologije, 1999)
Phase transformations and atomic transport processes characteristic for ion implanted and irradiated alloys are briefly presented and discussed. The paper starts with a short description of the basic process occuring during ion radiation of a solid. In the second part, some tipical examples of phase transformations in ion implanted metals are presented. The next section deals with the mechanism of atomic transport, several phenomena are discussed from simple ballistic collisions to atomic migration in non-uniform matrices containing the precipitates of insoluble atoms. Interest is focused on implanted iron-based alloys.
Keywords: zlitine; železo; ionska implantacija; obsevanje; fazni prehodi; transport snovi